2021
DOI: 10.1016/j.heliyon.2021.e07545
|View full text |Cite
|
Sign up to set email alerts
|

Breaking the barriers of animosity: innovation in business models as a positioning strategy

Abstract: Consumer animosity is often studied in the large economies of the world, in order to explain the negative feelings generated by an individual towards another country and its products, due to various political, economic and social conflicts. This study presents three specific developments in this field. First, to demonstrate how companies in the retail sector have been able to develop innovations in their business models through their shops and virtual channels, which generate a positive positioning in the mind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 56 publications
0
5
1
Order By: Relevance
“…The most important result of the research is that CE has a strong attitude-shaping effect in the case of homemade distillate, despite the fact that the difference between homemade distillate and pálinka is primarily of legal origin (Harcsa, 2016) and that pálinka is Hungary's national drink (Hungarikum), not homemade distillate. Our study showed the opposite effect of consumer ethnocentrism in the case of whisky, which did not confirm the research of Areiza-Padilla et al (2021). The consumer attitudes of ethnocentric Hungarian respondents towards whisky were counteracted by consumer ethnocentrism.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…The most important result of the research is that CE has a strong attitude-shaping effect in the case of homemade distillate, despite the fact that the difference between homemade distillate and pálinka is primarily of legal origin (Harcsa, 2016) and that pálinka is Hungary's national drink (Hungarikum), not homemade distillate. Our study showed the opposite effect of consumer ethnocentrism in the case of whisky, which did not confirm the research of Areiza-Padilla et al (2021). The consumer attitudes of ethnocentric Hungarian respondents towards whisky were counteracted by consumer ethnocentrism.…”
Section: Discussioncontrasting
confidence: 99%
“…Like in the case of the study of Areiza-Padilla et al. (2021) , the hypotheses follow the chapters of the literature.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Business ecosystems are the set of organizations made up of government agencies, customers, suppliers, competitors, distributors, among others, which manage to cooperate at the time of a delivery of product and/or service ordered by resorting to competition. Organizations achieve innovation through collaborations with adjunct organizations; this is how companies move beyond their traditional habitat forming organizations with different interests where they interact thanks to the Internet, creating opportunities for innovation and new challenges for well-established companies [ 1 ]. Innovative business ecosystems or also the so-called disruptive business models, are specific environments where a set of elements converge such as the availability of talented professionals, generation of knowledge, stakeholders, proximity to suppliers, among others [ 2 ].…”
Section: Introductionmentioning
confidence: 99%